Outcome of conjunctival flap surgery in case of non-healing corneal ulcer in a multi-specialty eye hospital of Northern Bangladesh - Khaja, M. Kamruzzaman; Islam, Khairul; Islam, M. Mahmud U.; Tumpa, Sonia A.; Huq, M. Sajidul (International Surgery Journal, 2023)
Background: This retrospective study evaluates the outcomes of conjunctival flap surgery for non-healing corneal ulcers at a tertiary eye hospital that were resistant to medical treatment. Methods: The study included 47 eyes of 47 patients with deep corneal ulcers who underwent conjunctival flap surgery in a multi-specialty eye hospital between April 2020 and January 2022. The follow-up period was 12 months. Primary outcome measures included the restoration of ocular surface integrity, while secondary outcomes assessed improvements in visual acuity and postoperative complications. Results: Among the 47 patients, 30 (63.82%) were male, and 17 (36.17%) were female, with a mean age of 52.13±14.91 years. The mean ulcer diameter was 4.52±2.02 mm, and the mean ulcer depth was 65±22.20% of the corneal thickness. An anatomic cure was achieved in 34 (72.34%) of the 47 eyes. Three eyes that failed to respond to conjunctival flap surgery required evisceration. Postoperative visual acuity improved in 15 eyes with peripheral ulcers. Common postoperative complications included flap retraction, flap necrosis, granuloma formation, and perforation. Conclusions: Conjunctival flap surgery is an effective treatment for non-healing corneal ulcers, providing ocular surface integrity and supporting corneal healing. It can potentially eliminate the need for emergency penetrating keratoplasty or prepare the eye for future optical keratoplasty.